Pengaturan Lampu Lalu Lintas Untuk Prioritas Jalan Pada Kendaraan Darurat Menggunakan Metoda Algoritma Even-Odd - Sugeng, Winarno (Jurnal Pekommas, 2023)
An emergency is a condition that must be dealt quickly. Fire and accident victims are one example of conditions that must be dealt quickly, but heavy traffic conditions severely hinder emergency vehicles on reaching locations, especially when dealing with a crossroad. A traffic light system that is capable of detecting the presence of emergency vehicles and prioritizing roads for emergency vehicles at a crossroad will greatly assist emergency vehicles in reaching locations that require a quick treatment. Even-Odd Algorithm is an algorithm that can be used to test a point whether the tested point is inside or outside the polygon. By implementing this algorithm, system can detect a vehicle location with GPS sensor that provides a coordinate point against the mapping area that called a system activation in detecting the presence of emergency vehicles at traffic light area. When the system detects the presence of emergency vehicles, system can immediately give a priority to the path where the emergency vehicle detected. With this detection system emergency vehicle can immediately get a priority to pass through the path, that will make an emergency situations served quickly. According to this research even-odd algorithm can be used to detect the location of emergency vehicle in mapping area.